KONSENTRASI KEPEMILIKAN SAHAM DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2014)
The study aims to: First, obtain empirical evidence about the impact of the concentration of stock ownership to the company's financial performance by using size of the compay and capital structure as a control variable in the Indonesia Stock Exchange. Second, obtain empirical evidence about the the impact of the company's financial performance to the concentration of stock ownership by using the size of the company and capital structure as a control variable in the Indonesia Stock Exchange. Third, obtain empirical evidence about the optimal concentration of share ownership in the Indonesia Stock Exchange. To achieve these objectives, the research conducted at the Indonesian Stock Exchange with a sample size as many as 195 companies and in explaining the relationship between the concentration of share ownership with the company's financial performance, firm size and capital structure as control variables and used t test, F test with Î± by 10 percent. Based on the results of research, the conclusions can be stated as follows: First, the concentration of share ownership and financial performance of the company can be placed as dependent and independent variables. The concentration of stock ownership have a significant positive effect on the company 's financial performance both before and after included firm size and capital structure as a control variable. Company's financial performance have a significant positive effect on the concentration of ownership of shares before and after included firm size and capital structure as a control variable. That is, the relationship between the concentration of share ownership with the company's financial performance is not a systematic relationship. Second, there is no an optimal concentration of share ownership, but there is a tendency of non- monotonic relationship between the concentration of share ownership with the company's financial performance. That is, the more concentrated the ownership of shares resulting majority shareholder actions that benefit themselves, to the detriment of minority shareholders